Immune responses and latent herpesvirus reactivation in spaceflight - Stowe, R P; Mehta, S K; Ferrando, A A; Feeback, D L; Pierson, D L (Aviation, space, and environmental medicine, 2001)
Increased frequency and severity of herpesvirus infections are common in individuals with impaired cellular immunity, a phenomenon observed in both the elderly and astronauts alike. This study investigated immune responses and latent herpesvirus reactivation during a 9-d spaceflight. In addition, adrenocortical and immune responses of an elderly astronaut (payload specialist-2, PS2; age 77) who flew on this mission were compared with that of younger crewmembers. Spaceflight and associated stresses will decrease cellular immunity and reactivate latent herpesviruses. Blood and urine samples, collected from the seven crewmembers who flew on the Space Shuttle Discovery (STS-95), were analyzed for levels of neuroendocrine hormones, leukocyte and lymphocyte subsets, and evidence of herpes-virus reactivation. Prior to flight, increased antibody titers to latent Epstein-Barr virus were found. During flight, acute changes in dehydroepiandrosterone sulfate (DHEAS) and cortisol resulted in a pronounced decrease in the DHEAS/cortisol ratio by the end of the mission for PS2 and a younger crewmember. Shedding of cytomegalovirus (CMV) in urine and increased CMV antibody titers also occurred inflight. At landing, the percent increases in adrenocorticotropic hormone and cortisol were greatest for PS2 as compared with the other six crewmembers. A significant neutrophilia also was observed in all crewmembers. Notably, PS2 had large increases in monocytes and natural killer cells at landing while other crewmembers showed little change or a decrease. These findings indicate that spaceflight and associated stresses reactivate latent herpesviruses and suggest that acute changes in neuroendocrine hormones mediate these changes in part by downregulating cellular immunity. Moreover, the similarities between aging and spaceflight suggest that the study of the immune system in elderly subjects may be useful as a predictive model for astronauts enduring long-term spaceflights.